1987
DOI: 10.1177/00220345870660021501
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Factors in Saliva: Ontogeny and Relation to Oral Health

Abstract: Antimicrobial agents (antibody and non-antibody) present in human saliva protect oral tissues by a variety of mechanisms, such as prevention of bacterial adhesion, agglutination of micro-organisms, and inhibition of multiplication and metabolism. However, studies in which the concentrations of various salivary antimicrobial agents have been correlated to the presence and severity of oral diseases--of dental caries, in particular--have produced controversial data, and it seems evident, also on the basis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 29 publications
2
64
0
3
Order By: Relevance
“…1A). Human submandibular and sublingual glands are mixed glands of serous and mucous cells (10,15,28), and CD14 protein was present only in serous cells and not in mucous cells of tissues from the submandibular gland as determined by immunohistochemistry (Fig. 1C).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…1A). Human submandibular and sublingual glands are mixed glands of serous and mucous cells (10,15,28), and CD14 protein was present only in serous cells and not in mucous cells of tissues from the submandibular gland as determined by immunohistochemistry (Fig. 1C).…”
Section: Discussionmentioning
confidence: 91%
“…The average daily flow of whole saliva amounts to 1 to 1.5 liters, and it has been suggested that another important protective factor is a constant flow of saliva from the mouth into the intestine (28). Therefore, we speculated that a more specific component responsible for systemic innate immunity acting against bacteria might be secreted from salivary glands into saliva.…”
mentioning
confidence: 95%
“…This can lead to substantial underestimation of peroxidase activity in persons with large amounts of salivary thiocyanate. Assays which eliminate this problem have been devised (Mansson-Rahemtulla et al, 1986), and they are now in common use (Tenovuo et al, 1987;Grahn et al, 1988;Rudney, 1989;Rudney et al, 1991). However, peroxidase activities measured in recent studies may not be fully comparable with those found in earlier studies.…”
Section: (D) Assay Methodsmentioning
confidence: 97%
“…Evidence for change is strongest for slgA in children. The secretory immune response takes several years to develop, and slgA levels are lower in infants and young children (EverharUUl., 1982;Alaluusua, 1983;Tenovuo et al, 1986aTenovuo et al, , 1987Smith et al, 1987;Gleeson et al, 1991). No such differences are apparent for salivary antimicrobial proteins (Tenovuo et al, 1986a(Tenovuo et al, , 1987.…”
Section: (D) Long-term Changementioning
confidence: 99%
See 1 more Smart Citation